The philosophy of early Christianity - Karamanōlēs, Giōrgos E. (Ancient philosophies, 2021)
"This book introduces the reader to the philosophy of early Christianity in the 2nd-4th centuries AD, and contextualizes the philosophical contributions of early Christians in the framework of the ancient philosophical debates. It examines the first attempts of Christian thinkers to engage with issues such as questions of cosmogony and first principles, freedom of choice, concept formation, and the body-soul relation, as well as later questions like the status of the divine persons of the Trinity. It also aims to show that the philosophy of early Christianity is part of ancient philosophy as a distinct school of thought, being in constant dialogue with the ancient philosophical schools, such as Platonism, Aristotelianism, Stoicism, and even Epicureanism and Scepticism. This book examines in detail the philosophical views of Christian thinkers such as Justin Martyr, Clement of Alexandria, Irenaeus, Tertullian, Origen, Basil and Gregory of Nyssa and sheds light in the distinct ways they conceptualized traditional philosophical issues and made some intriguing contributions. The book's core chapters survey the central philosophical concerns of the early Christian thinkers and examines their contributions. These range across natural philosophy, metaphysics, logic and epistemology, psychology and ethics, and include such questions as how the world came into being, how God relates to the world, what is the status of matter, how we can gain knowledge, in what sense humans have freedom of choice, what the nature of soul is and how it relates to the body, and how we can attain happiness and salvation. The Philosophy of Early Christianity is intended for undergraduate and postgraduate students of ancient philosophy and early Christianity, from across the disciplines of classics, history and theology"--